Survival nomogram for melanoma with bone metastasis based on the SEER database and an external validation cohort - Lu, Yuping; Chen, Lizhu; Zheng, Shicheng; Zhu, Li; Wu, Zhida; Chen, Yu; Lin, Jing (Frontiers in Oncology, 2025)
BackgroundWe aimed to develop and validate a comprehensive prognostic model for melanoma bone metastasis.MethodsData on melanoma bone metastasis patients were obtained from the SEER database and Fujian Cancer Hospital. Cox regression analysis was conducted to identify independent prognostic factors and to establish a Nomogram to predict the overall survival rate of patients.ResultsWe generated a Nomogram chart incorporating factors such as Age, Site, AJCC T stage, AJCC N stage, Surg Prim, Systemic and Sur Seq, Surg or Rad Seq, DX Brain, DX Liver, DX Distant LN, Tumor number, First malignant primary, Marital status, and Urban. The 1-year, 3-year, and 5-year OS rate AUCs for the training cohort were 0.715, 0.711, and 0.714, respectively, with a c-index of 0.656; the 1-year, 3-year, and 5-year OS rate AUCs for the internal validation cohort were 0.695, 0.725, and 0.719, respectively, with a c-index of 0.650; the 1-year, 3-year, and 5-year OS rate AUCs for the external validation cohort were 0.714, 0.791, and 0.842, respectively, with a c-index of 0.710. Calibration curves showed the consistency between the Nomogram’s observed and predicted prognostic outcomes.ConclusionOur model can be used to predict the prognosis of melanoma bone metastasis.